Learning English as a second language through children's literature with fifth grade students of the Unidad Educativa del Milenio "Guano" in the period 2022 - 2023. - Vizuete Fernández, Rina Natali (2024)
The main objective of this descriptive research study was to conduct a survey on students of 5th grade “A - B” at the Unidad Educativa del Milenio "Guano" during the academic year 2022 - 2023. To find out their preferences regarding children's literature before and after a two-week implementation. The methodology employed in this study is non-experimental, and assumes a descriptive and correlational level, applying a quantitative approach. All the data collected was set in Excel sheets and statistical tools were used in order to show the graphs of the results and their interpretation. In which it was concluded that the application of children's literature is not an issue addressed by all teachers in the area of English who believe that the readings during the class hours takes too much time. Therefore, many teachers do not apply Reading Lectures in their classes. Thus, based on the students' responses and results, it was concluded that the lectures are very effective in the acquisition of a foreign language. To conclude, it is highly recommended to apply children´s literature with more students in order to improve their acquisition of EFL.